"Kiss me with the hollow of your mouth" – imagining falling in love with Stense Andrea Lind-Valdan. Issue 3 (3rd September 2018) - Gade, Rune
ABSTRACT: The essay reflects upon the function of images within the love encounter, drawing on the personal experience of the author and his partner, visual artist Stense Andrea Lind-Valdan. Mixing personal experiences, diaristic notes and academic reflections, the essay moves beyond conventional scholarly style and experiments with more personal and anecdotal modalities, thus creating a text that re-enacts the fascination and imaginary entrapments involved in the love encounter while simultaneously reflecting upon these aspects of love.